Prevalence, Complications, and Risk Factors of Falls and Fear of Falling Among Older Adults; Based on Ardakan Cohort Study on Aging (ACSA) - Delbari, Ahmad; Azimi, Amirali; Najafi, Morvarid; Saatchi, Mohammad; Bidkhori, Mohammad; Bidkhori, Mohammad; Mousavi, Mohammad Ebrahim; Tabatabaei, Fatemeh-sadat; Hooshmand, Elham (Archives of Academic Emergency Medicine, 2023)
Introduction: The objective of this study was to assess the prevalence of falls, fear of falling (FOF), complications arising from falls, and identify possible sociodemographic and health-related factors associated with these outcomes among older adults. Methods: This cross-sectional study was based on the first wave of the Ardakan Cohort Study on Aging (ACSA), which includes participants over 50 years of age residing in Ardakan, Iran. Fall history, number of fall events, FOF, hospitalizations, and fractures in the past 12 months were assessed through a face-to-face interview. Health-related factors were recorded on a self-expressed basis. Associations were assessed using multiple logistic regression. Results: Among the 4,990 participants, fall history in the past 12 months was prevalent in 19.9%, with 10.1% reporting more than two fall events. Women (p < 0.001) and older participants (p< 0.001) had a higher prevalence. In females, 28.8% reported moderate to severe FOF, while 21% experienced disruptions in their daily activities as a result of this fear. The prevalence of fractures following falls was 5.1% in males and 8.6% in females. After adjusting for confounding factors, FOF (OR: 1.59, 95% CI: 1.33-1.91, p<0.001), imbalance (OR: 2.45, 95% CI: 1.68-3.58, p<0.001), urinary incontinence (OR: 1.44, 95% CI: 1.04-1.9, p=0.025), cognitive impairment (OR: 1.21, 95% CI: 1.01-1.46, p=0.049), vertigo or dizziness (OR: 1.39, 95% CI: 1.15-1.68, p<0.001), osteoporosis (OR: 1.24, 95% CI: 1.03-1.50, p=0.023), osteoarthritis (OR: 1.33, 95% CI: 1.13-1.56, p=0.001), depression (OR: 1.30, 95% CI: 1.06-1.60, p=0.010), and Central Nervous System (CNS)-affecting diseases (OR: 1.99, 95% CI: 1.33-2.97, p=0.001) were found to have positive associations with falls. Conclusion: This study showed that about one-fifth of those over 50 in Iran have experienced at least one fall within a year. Self-expressed imbalance, FOF, and urinary incontinence were the most prominent risk factors. Due to resulting in hospitalization and fractures, falls also lead to fear of falling and the associated limitation of activities.